The Quality of Islamic Religious Colleges: Ideal Format and Reality Conditions and Affecting Factors - Suradi, Ahmad; Nilawati, Nilawati (Jurnal Penelitian Pendidikan Islam, 2021)
This article describes how the quality of Islamic religious colleges and what factors influence them. The ideal format of Islamic religious colleges in achieving quality is the wider concept of science in the Islamic view; conceptualization; the existence of an academic community that has a soul of devotion, discipline, and critical understanding; selection of students as supporting the achievement of quality improvement; as well as academic traditions. In reality, the quality of Islamic religious college as a potential resource is still far from expectations. This happens, in addition to the low quality of education in Islamic religious colleges, also caused by the lack of effort and efforts of academic civitas reach toward quality. Thus, describing the conditions among them is the low education service and the low literacy ability of Islamic religious college students. Practically this reality shows that education in Islamic religious colleges today is experiencing many challenges and problems. Automatically these conditions have a direct impact with the resulting output. Due to the low quality of Islamic religious college education, the resulting low quality of graduates.